2014
DOI: 10.1071/mf13048
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional composition of potential zooplankton prey of the spiny lobster phyllosoma (Jasus edwardsii)

Abstract: Despite the global significance of spiny lobsters, the biology of their planktonic larvae, especially their carnivorous diet, is very poorly understood. Unsuitable diets and feeding regimes are one of the major reasons for consistently high mortalities during larval culture. In an effort to begin to determine the nutritional requirements of phyllosoma larvae of the spiny lobster, Jasus edwardsii, the present study first characterised the proximate composition of 11 previously identified groups of their potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 73 publications
4
30
0
1
Order By: Relevance
“…This is supported by previous studies on the natural diets of phyllosoma, that suggest a preference for soft, gelatinous zooplankton (Jeffs, 2007;Saunders and Thompson, 2012;Wang et al, 2014b) which contain proximate nutrients in a highly digestible format (Jeffs et al, 2004). Thus, the administration of predigested protein has the potential to alleviate the limited digestive ability of larvae by imitating the nutritional format of their natural prey sources (Johannsdottir et al, 2014;Kvale et al, 2002;Rønnestad et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
“…This is supported by previous studies on the natural diets of phyllosoma, that suggest a preference for soft, gelatinous zooplankton (Jeffs, 2007;Saunders and Thompson, 2012;Wang et al, 2014b) which contain proximate nutrients in a highly digestible format (Jeffs et al, 2004). Thus, the administration of predigested protein has the potential to alleviate the limited digestive ability of larvae by imitating the nutritional format of their natural prey sources (Johannsdottir et al, 2014;Kvale et al, 2002;Rønnestad et al, 2003).…”
Section: Discussionsupporting
confidence: 65%
“…The results of the current study confirmed that there is pronounced lipid accumulation from Stage VI to VIII in phyllosomas of P. cygnus. This result suggests a possible change in diet in late-stage phyllosomas to prey with a high lipid yield, such as krill, as there is a narrow range of potential zooplankton prey in the wild with high lipid content (Saunders et al 2012;Wang et al 2013).…”
Section: Developmental Stagesmentioning
confidence: 96%
“…We posed the question as to why, in our recent work, rock lobster phyllosoma in CCEs are significantly healthier, with larger lipid stores, than those in WCEs (Wang et al , ). We hypothesized that CCEs were more productive than WCEs, but we disprove this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…However, phyllosomas are not usually found within the LC at this time, as most phyllosomas remain offshore and further south, in cooler and (at this time) less nutrient‐rich subtropical waters (STW). There are a number of possible explanations for this spatial mismatch of phyllosomas and their prey, including an improved availability or quality of food in STW (Wang et al , b , ), offshore reduction in predation on evolutionary time scales (Wasmund et al ; Säwström et al ), or improved opportunity to be transported or recruited to more desirable locations on the coast (Caputi ).…”
mentioning
confidence: 99%